2022
DOI: 10.3389/fendo.2022.942368
|View full text |Cite
|
Sign up to set email alerts
|

Identification and analysis of novel endometriosis biomarkers via integrative bioinformatics

Abstract: Endometriosis is a gynecological disease prevalent in women of reproductive age, and it is characterized by the ectopic presence and growth of the eutopic endometrium. The pathophysiology and diagnostic biomarkers of endometriosis have not yet been comprehensively determined. To discover molecular markers and pathways underlying the pathogenesis of endometriosis, we identified differentially expressed genes (DEGs) in three Gene Expression Omnibus microarray datasets (GSE11691, GSE23339, and GSE7305) and perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 84 publications
0
7
0
Order By: Relevance
“…Further, a possible role of the degradation and remodeling of the extracellular matrix in endometriosis datasets has been revealed in our study. Endometriotic tissues have been shown to be significantly associated to extracellular matrix reorganization in some studies, which may explain some of the molecular mechanisms underlying the progression of the disease [47][48][49][50]. Regarding uterine leiomyomas, we were able to detect some significantly enriched biological processes that have been previously reported in association with the disease such as hormone secretion and cell signaling [51].…”
Section: Discussionmentioning
confidence: 51%
“…Further, a possible role of the degradation and remodeling of the extracellular matrix in endometriosis datasets has been revealed in our study. Endometriotic tissues have been shown to be significantly associated to extracellular matrix reorganization in some studies, which may explain some of the molecular mechanisms underlying the progression of the disease [47][48][49][50]. Regarding uterine leiomyomas, we were able to detect some significantly enriched biological processes that have been previously reported in association with the disease such as hormone secretion and cell signaling [51].…”
Section: Discussionmentioning
confidence: 51%
“…Bae et al recently identified differentially expressed genes (DEGs) in three gene expression omnibus microarray datasets in endometriotic tissues [44]. In this study, a total of 135 DEGs were detected in each dataset, mostly belonging to signaling pathways associated with inflammation, complement activation, cell adhesion, and the extracellular matrix.…”
Section: Endometriosismentioning
confidence: 80%
“…Interestingly, it has been shown that LY96 has also been suggested as a diagnostic marker for SLE (37).Likewise, the study concluded that LY96 is believed to have a signi cant impact on in ammatory and immune-related diseases, including rheumatoid arthritis, Crohn's disease, and in ammatory diabetic cardiomyopathy(38-40). Bae et al further veri ed the high expression of the LY96 gene in EMS by immunohistochemistry and western blot analysis, concluded that TLR4/NF-κB and Wnt/frizzled signaling pathways, as well as estrogen receptors, regulate the progression of EMS (41). Bao Guo et al suggested that activation of the TLR4 signaling pathway promotes the recruitment and activation of immune cells, triggering a local in ammatory response, leading to the secretion of in ammatory factors (e.g., TNF-α) and growth factors (e.g., VEGF), which stimulate the proliferation of endometrial cells, invasion, and cause further tissue damage (42).Therefore, we hypothesize that the shared pathogenesis of EMS and SLE is mediated by the TLR4 signaling pathway.…”
Section: Discussionmentioning
confidence: 99%